How blockchain renovate the electric vehicle charging services in the urban area? A case study of Shanghai, China. (15th September 2021) - Fu, Zhengtang; Dong, Peiwu; Li, Siyao; Ju, Yanbing; Liu, Hanbo
Abstract: With the sustainable development of cities, green transportation is regarded as a critical approach to mitigate air pollution and greenhouse gas emissions. Driven by this, Electric vehicles (EV) have been strongly advocated by the government for their zero-emission merit. However, the promotion of EV is not smoothly caused by inconvenient charging issues. For the high construction cost and land scarcity, current public charging stations could not meet the booming charging demands and worry the potential EV users. To address the problem, this paper proposed a peer-to-peer (P2P) private charging pile sharing system supported by blockchain technology. In this system, the charging records of EV users could be packaged and uploaded into the blockchain, which is immutable and tamper-resistant. The detailed blockchain hierarchy is also designed to make this system more practical. Meanwhile, the Multi-Agent-Based (MAB) model is adopted to evaluate the performance of this sharing system. In this model, different participants' behaviors are fully considered and calculated. Furthermore, several numerical experiments are conducted to unveil the inner business relationships between charing demanders and pile suppliers. Lastly, the proposed private pile sharing system is validated by the realistic data of the Lujiazui business circle in Shanghai, China. Graphical abstract: Image 1 Highlights: We proposed a novel P2P EV pile sharing system supported by blockchain. Multi-agent modeling is adopted to evaluate this decentralized sharing system. The practical architecture and hierarchy are well designed for this system. The proposed framework is validated by the real data set of Shanghai, China.